2014
DOI: 10.3758/s13415-014-0297-4
|View full text |Cite
|
Sign up to set email alerts
|

Adult age differences in frontostriatal representation of prediction error but not reward outcome

Abstract: Emerging evidence from decision neuroscience suggests that although younger and older adults show similar frontostriatal representations of reward magnitude, older adults often show deficits in feedback-driven reinforcement learning. In the present study, healthy adults completed reward-based tasks that did or did not depend on probabilistic learning, while undergoing functional neuroimaging. We observed reductions in the frontostriatal representation of prediction errors during probabilistic learning in older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
124
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(144 citation statements)
references
References 51 publications
15
124
5
Order By: Relevance
“…For example, a recent study showed that ventral striatal activity was increased in older adults when receiving reward but not during anticipation (Vink et al 2015). This is also consistent with findings indicating that representation of reward outcome is stable in aging, compared with representation of prediction error (Samanez-Larkin et al 2014). Thus, despite the well-documented decline in dopaminergic activity in older adults (for review, see Li and Rieckmann 2014), it is possible that at least a subset of older adults exhibit enhanced processing of rewarding information, however, this account remains speculative.…”
supporting
confidence: 76%
“…For example, a recent study showed that ventral striatal activity was increased in older adults when receiving reward but not during anticipation (Vink et al 2015). This is also consistent with findings indicating that representation of reward outcome is stable in aging, compared with representation of prediction error (Samanez-Larkin et al 2014). Thus, despite the well-documented decline in dopaminergic activity in older adults (for review, see Li and Rieckmann 2014), it is possible that at least a subset of older adults exhibit enhanced processing of rewarding information, however, this account remains speculative.…”
supporting
confidence: 76%
“…Task-related activity in the fronto-striatal circuit was also affected by age, where older adults generally showed stronger responses to factual and counterfactual consequences in the striatum, but a non-significant correlation with reward predictions in the vmPFC. Our findings are in general agreement with previous literature showing that relatively poor decision making in multialternative choice tasks in older adults is related to aberrant reward prediction and prediction error processing in this fronto-striatal circuit (Chowdhury et al, 2013;Eppinger, Walter et al, 2013;Eppinger, Nystrom, et al, 2012;Eppinger, Schuck, et al, 2013;Grady, 2012;Hedden & Gabrieli, 2004;Rademacher, Saalma, Grunder, & Sprecklemeyer, 2014;SamanezLarkin et al, 2007;Samanez-Larkin et al, 2011;Samanez-Larkin et al, 2014;Samanez-Larkin & Knutson, 2015;Vink et al, 2015;), and extends these findings to include altered processing of counterfactual consequences. Finally, this study advocates the modelbased fMRI experimental design to study both behavioral and neural systems for decision making between age groups but cautions that model fits be carefully taken into account when drawing conclusions about group differences.…”
Section: Discussionsupporting
confidence: 82%
“…This reward prediction error (RPE) signal is thought to have an interplay with prefrontal cortical areas such as the prefrontal cortex (PFC) and the anterior cingulate cortex (ACC) [14,17,18]. This frontostriatal circuit with dopaminergic activation plays an essential role in reward seeking behavior and decision making [19,20], and the ERPs related to feedback evaluation, like the FRN and the reward positivity, are assumed to be the correlates of the activity of this dopaminergic circuit [17,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…This reward prediction error (RPE) signal is thought to have an interplay with prefrontal cortical areas such as the prefrontal cortex (PFC) and the anterior cingulate cortex (ACC) [14,17,18]. This frontostriatal circuit with dopaminergic activation plays an essential role in reward seeking behavior and decision making [19,20], and the ERPs related to feedback evaluation, like the FRN and the reward positivity, are assumed to be the correlates of the activity of this dopaminergic circuit [17,21,22].The FRN occurring at approximately 250 ms after feedback onset corresponds mainly to the erroneous nature of the outcome [22,23]. Contrary to this, the reward positivity (occurring in a similar time window as the FRN) is elicited by positive feedback informing about reward [24][25][26].…”
mentioning
confidence: 99%
See 1 more Smart Citation